The effect of supplementation with selected micronutrients on dementia and osteoporosis - Soliman, Rafik (AUC Knowledge Fountain, 2020)
People had done everything they are capable of to stay young; however, aging is a definite process that could not be tricked. Aging results in cognitive memory impairments and osteoporosis which affects mobility. Memory impairment is the inability to encode information. It has been common to hear people complaining from this disease not only in the process of aging but also at young ages. That is why this topic has been grabbing the attention of not only concerned candidates but also scientists and media. In this study, we will tackle both dementia and osteoporosis, where in the first arm Alzheimer’s disease was chemically induced in rats using aluminum chloride (AlCl3) and in the second arm we used ovariectomized mice as an osteoporosis model. Rodents were divided into five groups in each study; group 1, the negative control group; where rats/mice were administered regular diet only, group 2; the positive control group not consuming any premixes were either AlCl3 treated or ovariectomized rodents for dementia and osteoporosis studies, respectively. Group 3 were AlCl3 treated or ovariectomized and fed with a premix of micronutrients with the European Food Safety Authority (EFSA) authorized claims of positively improving cognitive abilities or osteoporosis (ingredients that are authorized by the EFSA and supported by scientific research). Group 4 were AlCl3 treated or ovariectomized and fed with a premix of micronutrients with content claim that possess health claims not authorized yet by EFSA, however it is based on potential scientific studies. Group 5 were AlCl3 treated or ovariectomized and fed with a master mix, the combination of all ingredients consumed by groups 3 and 4. This research aimed to test the prevention and/or suppression of Alzheimer’s Disease and Osteoporosis. For this purpose, dementia study tested results through Morris Water Maze (MWM), Enzyme-Linked Immunosorbent Assay (ELISA) and histopathological examination of the rats’ brain, while for osteoporosis results were tested though detection of blood calcium (total & ionized) and Alkaline Phosphatase (ALP) and histopathological examination of mice femur bone. In this context, results for both studies demonstrated that supplementation with the selected vitamins and minerals improved prevention of AD and osteoporosis. In the dementia study, the three premixes given showed better results compared to positive control in the behavioral testing and Amyloid β-42 biomarker testing, specifically group 4 which showed the best performance. In the osteoporosis, the detection of blood calcium (total & ionized) and alkaline phosphatase (ALP) did not show indicative results, that is why more testing through histopathological examination of mice femur bone was done showing good results by the consumption of the premixes. To conclude the premixes consumed in these two studies show potential in fighting dementia and osteoporosis, while some premixes have shown better results than others.